Lavender (Lavandula offitcenalis L) cultivation technology and medicinal properties (Texas Journal of Medical Science, 2023)
In this article, the cultivation technology, biology, importance in agriculture and agriculture, chemical composition and medicinal composition of the lavender plant are covered